PILRA polymorphism modifies the effect of APOE4 and GM17 on Alzheimer’s disease risk - Karin Lopatko Lindman; Caroline Jonsson; Bodil Weidung; Jan Olsson; Janardan P. Pandey; Dmitry Prokopenko; Rudolph E. Tanzi; Göran Hallmans; Sture Eriksson; Fredrik Elgh; Hugo Lövheim (Scientific Reports, 2022)
Abstract PILRA (rs1859788 A > G) has been suggested to be a protective variant for Alzheimer’s disease (AD) and is an entry co-receptor for herpes simplex virus-1. We conducted a nested case–control study of 360 1:1-matched AD subjects. Interactions between the PILRA-A allele, APOE risk variants (ε3/ε4 or ε4/ε4) and GM17 for AD risk were modelled. The associations were cross-validated using two independent whole-genome sequencing datasets. We found negative interactions between PILRA-A and GM17 (OR 0.72, 95% CI 0.52–1.00) and between PILRA-A and APOE risk variants (OR 0.56, 95% CI 0.32–0.98) in the discovery dataset. In the replication cohort, a joint effect of PILRA and PILRA × GM 17/17 was observed for the risk of developing AD (p .02). Here, we report a negative effect modification by PILRA on APOE and GM17 high-risk variants for future AD risk in two independent datasets. This highlights the complex genetics of AD.